PENINGKATAN KEMAMPUAN MENULIS TEKS BERITA MELALUI TEKNIK TIRU MODEL PADA SISWA KELAS VIII 2 MADRASAH TSANAWIYAH NEGERI KOTO TANGAH PADANG - Rifdawati Rifdawati (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The purpose of this study is to describe and explain the process of improving the ability to write a text message via a technique to imitate a model for students of classes VIII 2 MTsN Koto Tangah Padang. Hypothesis is the application of techniques to imitate the model can improve the ability to write news text eighth grade students MTsN Koto Tangah Padang. This study consisted of two cycles, the first cycle consists of two meetings, the first meeting focused on understanding concepts and imitation model of news which are presented to the students. The second meeting which students perform text editing news had written. In this first cycle turns the students do not understand the main points contained in the news. For the second cycle of change that is done by marking the headlines that made the model so that students truly know the report text which included the subject in the news.